Canadian Recommendations for Germline Genetic Testing of Patients with Breast Cancer: A Call to Action - Evan Weber; Carlos A. Carmona-Gonzalez; Melanie Boucher; Andrea Eisen; Kara Laing; Jennifer Melvin; Kasmintan A. Schrader; Sandeep Sehdev; Stephanie M. Wong; Karen A. Gelmon (Current Oncology)
Pathogenic variants in breast cancer predisposition genes are associated with poor clinical outcomes but also offer an opportunity for more individualized therapeutic pathways. Given increasing knowledge, improvements in germline genetic testing efficiency, and the availability of novel systemic targeted treatment options, the importance of appropriately identifying patients for testing has never been greater. A pan-Canadian expert working group (EWG) consisting of 10 healthcare professionals (HCPs) was convened to review recent international guidelines for germline genetic testing in breast cancer and develop Canadian recommendations. The group identified four clinical questions to address which patients should undergo testing, what approaches should be used, how patients should be counselled, and what steps are needed for implementation. In response to these questions, the EWG agreed upon 12 recommendations that emphasized broader incorporation of germline genetic testing and more standardized, streamlined testing and counselling approaches. The group also offered multiple suggestions to support effective and equitable implementation across Canada. These recommendations provide guidance for HCPs and represent a call to action for the Canadian government and other organizations to support genetic testing pathways, drug access, and ultimately improved outcomes for patients with breast cancer and their families.